Learning styles as predictors of Iranian EFL Children’s self-esteem and anxiety - Zarei, Abbas Ali; Esfandiari, Rajab; Keshavarz, Zohreh (Journal of Learning Styles, 2017)
The present study was conducted to investigate learning styles (Visual, auditory, kinesthetic, tactile, individual, and group) as predictors of self-esteem and anxiety. The participants were 90 male and female young EFL learners studying English at a language institute in Qazvin, Iran. The instruments included Young Learners English Starter test (YLE), Young EFL Learners’ Learning Style Questionnaire, Self-Esteem Inventory, and Foreign Language Classroom Anxiety Scale (FLCAS). Data were analyzed through correlation coefficient and multiple regression analyses. Results indicated that auditory style had predictive power on self-esteem, but none of the six learning styles could predict anxiety. There was also a significant correlation between learners’ self-esteem and anxiety. The present study can have implications for teachers, syllabus designers, material developers, and researchers.